Rapid Recovery and Short‐Term Culture of Gastric Circulating Tumor Cells Using Microcavity Array - Tomoko Yoshino; Tomohiro Takabayashi; Qian Bao; Tsuyoshi Tanaka; Ryo Negishi; Tatsu Shimoyama; Takeshi Sawada; Yusuke Kanemasa; Fumiaki Koizumi (Engineering in Life Sciences, 2025)
ABSTRACT Circulating tumor cells (CTCs) hold significant promise for cancer diagnosis, prognosis, and treatment monitoring. We previously developed a technique for a single‐cell filtering device known as the microcavity array (MCA), specifically designed for the efficient recovery of CTCs from whole blood samples. Efficient enrichment and release of cells from the MCA remains challenging because of cell adhesion that occurs on the MCA surface during the enrichment phase. This study investigated the effects of surface modification with 2‐methacryloyloxyethyl phosphorylcholine (MPC) on the recovery efficiency of cancer cell lines from MCA. Scanning electron microscope (SEM) demonstrated reduced cell‐substrate interactions, leading to improved recovery efficiency. Comparative analyses showed that the MCA method provided superior recovery efficiency and reduced processing time compared to traditional methods such as density gradient centrifugation (DGC), while maintaining cell viability and proliferative capacity. CTCs were successfully detected in patients with gastric cancer, and short‐term cultures were achieved even when fewer than 20 CTCs per milliliter of blood were isolated. These findings emphasize the importance of surface modification for enhancing CTC isolation and the need for optimized culture conditions. The optimized MCA method offers a promising approach for rapid CTC recovery and potential integration with automated systems. Practical application: The Microcavity array (MCA) is a device specifically designed for efficient recovery of CTCs from whole blood. However cell adhesion on the MCA surface can limit release efficiency. This study demonstrated that surface modification with MPC signigicantly reduces cell‐substrate adhesion, improving recovery efficiency while maintaining cell viability and proliferative capacity. Compared to traditional density gradient centrifugation, the MPC‐modified MCA offers shorter processing time and better performance. CTCs were successfully detected in gastric cancer, and short‐term cultures were achieved even when fewer than 20 CTCs per mL of blood were isolated. The method supports downstearm applications such as cancer cell characterization and treatment monitoring. With potential for integration into automated system, the optimized MCA provides a practical, scalable solution for clinical liquid biopsy and personalized oncology.